Research and Development in Magnesium Alloys for Industrial and Biomedical Applications: A Review - Ramalingam, Vaira Vignesh; Ramasamy, Padmanaban; Kovukkal, Mohan Das; Myilsamy, Govindaraju (Metals and materials international, 2020)
The work reviews the research and development status of magnesium alloy, with more attention to the methodologies and technologies adopted to improve the properties of AZ91 alloy. The drive force of utilizing magnesium alloys for automotive and biomedical application is light weightiness and biocompatibility respectively. However, the softness and high activity of magnesium alloys result in high wear and high corrosion rate respectively. One of the essential factors influencing the properties of magnesium alloy is its microstructure. Consequently, the grain size, morphology and distribution of phase constituents influence the properties of magnesium alloys. The modification of microstructure through processing route (hot working and cold working), heat treatment, and alloying elements improves the mechanical, corrosion, biocompatible, and tribological properties of magnesium alloys. Besides microstructural modification processes, addition of reinforcements, and coatings improves the properties of magnesium alloys. This article emphasis on the recent research on the technologies to improve the microstructure, hardness, tensile strength, ductility, yield strength, wear resistance, and corrosion resistance of magnesium alloy AZ91. Moreover, this review addresses the key issues hindering the applications of magnesium alloys for structural and biomedical applications. Graphic Abstract